Analisis Niat Beli Kembali Produk Tabungan Emas di Pegadaian Dalam Konteks Omnichannel - Romindo Megawati Pasaribu; Senti R.O Pasaribu; Imelda Sitinjak; Herry D.S Pasaribu; Vinsensius Matondang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Omnichannel is a business model in which its operations and services are integrated in all sales channels owned by the company in one overall system. Omnichannel combines all store marketing channels both online and offline which can make it easier for customers to find information, process, and make decisions in making product purchases. The purpose of this study was to analyze customer engagement as a mediating variable between channel integration quality and repurchase intention on gold savings products at Pegadaian Medan. The sample in this study was 90 respondents and this sampling method used accidental sampling technique. The data analysis method to answer the hypothesis uses SmartPLS 3.0. The results showed (1) Customer engagement in the omnichannel context had a significant effect on repurchase intention, (2) Channel integration in the omnichannel context had no positive and insignificant effect on customer engagement, (3) Channel integration had a positive and significant effect on purchase intention.